REVIEWS - Meyers, Carol L. (Journal of Semitic studies, 2003)
The Elders of the City: A Study of the Elders-Laws in Deuteronomy (Society of Biblical Literature Monograph Series 55) Timothy M. Willis , Society of Biblical Literature, Atlanta 2001. Pp. xiii + 353. Price: $45.00 . ISBN: 1-58983-013-X.